Determination of the prevalence of childhood allergic conjunctivitis in eight elementary schools in the Southern Cone of Lima, Peru - Carrión Ojeda, Carlos (2010)
Introduction: In Lima with a population of almost three million children it has been not reported until now child allergy prevalence studies. Objectives: To determine the current epidemiological characteristics of childrens eye allergy in the poor elementary students in South of Lima. We took significant sample to students from 8 primary schools in three districts in the South of Lima, with 120,000 children. Material and method: A cross-sectional and observational study was made, assessed and considered, on-site at each school 2,011 elementary students. For the calculation of samples we use Excel 2003 and for analysis we use SPSS 15.0. Results: With an increase in the frequency of eye allergy that increases with age. Eye allergy is more correlated with the blepharitis and the chalazion. Conclusions: The prevalence of eye allergy 16.3% is moderate in the primary school population of Lima South, the eye allergy behavior is rising as advances school age (Y = 0.0305 X=0.0638); It could be related to a longer exposure to allergens, as well as the lifestyle of the teenage pre peculiarities.